Les apprenants utilisent cet ordre souvent: Early stages in the acquisition of adverb placement and negation in L2 French - Balcom, Patricia (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 2013)
Within current SLA research in the generative framework, Full Transfer Full Access (Schwartz and Sprouse 1996, henceforth FTFA) is an influential model which aims to account for the initial state in adult L2 acquisition. There are two parts to FTFA. Full transfer means that the complete L1 grammar is the initial state in L2 acquisition. When the L2 input cannot be accommodated by the transferred L1 properties, learners have full access to UG, which allows them to entertain other hypotheses and constrains the restructuring of their Interlanguage grammars. In this paper I will explore the earliest stages of the L2 acquisition of adverbs and negation in L2 French in light of the predictions of FTFA.